Disease-Specific Enteric Microbiome Dysbiosis in Inflammatory Bowel Disease - Mirsepasi-Lauridsen, Hengameh Chloé; Vrankx, Katleen; Engberg, Jørgen; Friis-Møller, Alice; Brynskov, Jørn; Nordgaard-Lassen, Inge; Petersen, Andreas Munk; Krogfelt, Karen Angeliki (Frontiers in Medicine, 2018)
Inflammatory Bowel disease (IBD) is traditionally divided into Crohn´s disease (CD) and ulcerative colitis (UC). UC is a relapsing non-transmural inflammatory disease that is restricted to the colon and is characterized by flare-ups of bloody diarrhea. CD is a chronic, segmental localized granulomatous disease that can affect any part of the entire gastrointestinal tract. Ileo-anal pouch is a procedure restoring functionality of the rectum after a colectomy. IBD is a multifactorial disease and flares of IBD are probably triggered by changes in the intestinal microbiota followed by an abnormal immune response. In this study, we aim to analyze the intestinal bacterial diversity in IBD patients during different stages of disease in comparison to healthy controls. Permission for human experiments and recruitment of participants was obtained from the Ethic Committee for Copenhagen County hospitals (Permission no. KA-03019, Permission no. KA-20060159). Stools from 26 healthy controls, 42 CD, 38 UC and 18 pouch patients were collected. Stool DNA extraction was performed using Qiagen, DNA mini stool kit Denmark. DGGE-PCR amplifying the V2-V3 region of 16S-rDNA gene of the bacteria was amplified by universal primer HDA1 and HDA2. Analysis of DGGE was performed blinded using BioNumerics version 7.5. After normalization, a DGGE gel band matching was performed. The similarities between profiles were calculated with a ranked Pearson correlation coefficient based on the band matching results using band intensities. Simpson´s index of diversity and Pielou species evenness were calculated. Based on the Shannon Diversity Index UC patients had a lower species diversity and bacteria evenness in comparison to healthy persons, p<0.05. However, only CD and disease pouch patients had lower species diversity compared to those with inactive disease and healthy controls. Well-functioning pouch patients had decreased species evenness in comparison to disease pouch patients and control group. During the active disease stage in CD and pouch, the patients have a low bacterial diversity in their gut when compared to the inactive stage. In UC patients, a general low diversity was observed at all stages of the disease compared to healthy controls.